Telehealth to the Rescue During COVID-19: A Convergent Mixed Methods Study Investigating Patients' Perception - Al-Sharif, Ghadah A.; Almulla, Alia A.; AlMerashi, Eman; Alqutami, Reem; Almoosa, Mohammad; Hegazi, Mona Zakaria; Otaki, Farah; Ho, Samuel B. (Frontiers in Public Health, 2021)
The onset of the pandemic necessitated abrupt transition to telehealth consultations. Although there are a few tools that gauge the patients’ perception about their experiences, none of them are contextualized to an emergency in the Middle-East-and-North-Africa-region. Accordingly, this study aims at developing and validating a tool to address this gap, and deploying it to assess the patients’ perception of telehealth services during COVID-19 in Dubai, United Arab Emirates (UAE). A convergent mixed methods design was adapted. A random selection of 100 patients from Dubai, UAE were invited to participate. Qualitative and quantitative datasets were collected using a tailor-made survey. The qualitative data, collected through open-ended questions, was analyzed using multi-staged thematic analysis. As for the quantitative data, it captured the patients’ extent of satisfaction, and was assessed using SPSS (with a series of descriptive and inferential analyses). The qualitative and quantitative findings were then merged via joint display analysis. Out of the 100 patients that were randomly selected, 94 patients participated in this study. The reliability score of Cronbach’s Alpha for the instrument was 98.9%. The percentage of the total average of satisfaction was 80.67%. The Principal Component Analysis showed that 88.1% of the variance can be explained by the instrument (p<0.001). The qualitative data analysis expanded upon the quantitative findings enabling a better understanding of the patients’ perception. Three themes, revolving around the quality of the patient telehealth experiences, surfaced: ‘Factors that worked to the benefit of the patients’, ‘Factors that the patients were not in favor of’, and ‘Opportunities for improvements as perceived by the patients’. This study introduced a novel patient satisfaction with telehealth consultation survey contextualized to the COVID-19 times in Dubai, UAE. The participants were quite satisfied with the quality of their experience, however they suggested areas for improvement. Regional healthcare decision-makers can leverage the identified advantages and opportunities for improvement of telehealth. This will enable making informed decisions regarding the continuity of telehealth irrespective of how matters unfold in relation to the pandemic. It will also better prepare the healthcare sector for potential resurgence(s) of COVID-19 and/ or the occurrence of other similar emergencies.